Negotiating Celebrity Femininity in Three Auto/Biographies of Indonesian Female Celebrities - Aquarini Priyatna (Universitas Airlangga, 2016)
AbstrakMelalui auto/biografinya, selebritas perempuan Indonesia Krisdayanti, Yuni Shara, dan Tiara Lestari menampilkan femininitas yang global dan lokal, dan menunjukkan negosiasi yang kompleks antara berbagai keharusan berkenaan dengan kesopanan, peran sebagai ibu, dan normalitas, serta tuntutan global yang berkenaan dengan seksualitas, selebritas dan universalitas. Femininitas ditunjukkan baik sebagai suatu hal yang bersifat normatif maupun sebagai suatu hal yang disruptif, dengan memperluas dan mengubah ruang yang mendefinisi makna menjadi seorang perempuan, dalam konteks yang saling berkaitan antara kebudayaan lokal Indonesia, budaya selebritas dan globalisasi. Artikel ini berkontribusi terhadap berbagai pemahaman atas globalisasi serta proses, efek dan dampaknya sekaitan dengan konstruksi gender melalui fenomena khusus auto/biografi selebritas Indonesia. Lebih khusus lagi, artikel ini berargumentasi bahwa auto/biografi merupakan ruang yang penting untuk memahami bagaimana media dimanfaatkan dan merupakan bagian integral dari konstruksi citra dan representasi selebritas perempuan di dalam konteks lokal tertentu dan dalam konteks yang lebih global. Kata kunci: selebritas, femininitas, auto/biografi, lokalitas, globalitas AbstractThrough their auto/biographies, Indonesian female celebrities, i.e. Krisdayanti, Yuni Shara and Tiara Lestari, present femininities that are both global and local and reveal complex negotiations of local imperatives of modesty, maternity and normality and global imperatives towards sexuality, celebrity and universality. Femininity is performed both as normative and disruptive, extending and altering the space of what it means “to be a woman” within the intersecting contexts of local Indonesian culture, celebrity culture and globalization. This paper used the term auto/biography as a method to embrace a more inclusive term that include writings that fall between the category of autobiography and biography. While the standard normative idea of autobiography refers to writings about oneself as written by oneself, and the definition of biography to writings about oneself as written by others, the term auto/biography used here accommodates the complexities of authorship as well as depiction of the auto/biographical subjects. This paper contributes to understandings of globalization and its gendered processes, effects and impacts through the particular phenomenon of the auto/biographies of Indonesian female celebrities. Particularly, this paper argues that auto/biography has become an important space to understand how media is used and an integral part of the construction of female celebrity’s image and representation within a certain local and the more global context at the same time. Keywords: auto/biographies, celebrity, femininity, globality, locality